INVESTIGATION OF FACULTY EMOTIONS DURING THE COVID-19 PANDEMIC AND THE STRATEGIES TO ASSURE THEIR EMOTIONAL WELL-BEING (Proceedings of the International Conference on Education, 2021)
This paper analyses faculty’s emotions during the Covid-19 pandemic and identifies their characteristics and possible emotional vulnerability in order to provide decision makers with the information necessary to better serve this community. This action is important since teaching is catalogued as the fourth most stressful profession in the world, and due to adverse conditions, this could increase, as reported by the literature. This research, carried out in Mexico during April 2020, answers the questions: What are the main concerns of instructors at the beginning of the COVID-19 lockdown in a private Mexican university? What are their perceptions about their health and the demographic characteristics of these instructors during the COVID-19 lockdown? We conducted a survey for 104 professors of the South-Centre Region of the Tecnologico de Monterrey and the results were analysed using a mixed methodology which included text analysis and descriptive and inference statistics. Results indicated that the mayor concerns were health, getting sick, contagion and uncertainty. Other concerns included socio-economic consequences of lockdown and their teaching performance under the online modality. Regarding health, the faculty reported feeling more frequently concerned, followed by feeling calm, excellent, at risk and vulnerable and 36% revealed having negative feelings regarding their health. Based on their generation, negative feelings increased the older the faculty member was, from 28% of Millennials to 55% of Boomers. Main concerns of professoriate are dependent of gender and generation; however, these are independent of the academic degree, the professional experience and the relationship status. Furthermore, we mention the strategies implemented by the Tecnologico de Monterrey to assure the emotional wellbeing of its faculty.
Keywords: Faculty concerns; Proffesors well-being; support during pandemic; higher education; educational innovation